Melting of polymer blends and concomitant morphology development in single screw extruders - Cunha, S. M. (2010)
The current understanding of the melting stage in single screw extruders results from pioneering research efforts that were initiated in the fifties and continued for more than thirty years. Most of these theoretical and experimental studies used homopolymers as model systems, whereas in industrial practice there has been a considerable evolution in terms of the complexity of the materials being extruded. This work reports an attempt to monitor the melting sequence and the morphology development of immiscible physical and chemically compatibilized PA6/PP blends. A hybrid melting mechanism, incorporating elements of the Tadmor and of the Dispersive melting mechanisms seems to develop; the early stages of morphology development seem to be similar to those observed in the Haake mixer and Twin-screw extruder.